Content Analysis of Goverment Regilation Number 94 of 2021 in Improving Public Services in Batuatas District - Zulfikar Putra (IJRAEL: International Journal of Religion Education and Law, 2023)
This study aims to analyze the content of regulations regarding Civil Servant Discipline Based on Government Regulation No. 94 of 2021 at the Batuatas District Office. 94 of 2021 at the Batuatas District Office. This research uses a descriptive method with a qualitative approach with observation, interview and documentation techniques. The findings of the research results that there are still government employees of Batuatas Subdistrict who do not carry out the mandate of the regulations regarding Employee Discipline, including not being on time when entering the office, not being friendly in service and often ignoring their duties. Through this research, it is hoped that the discipline of Batuatas Sub-district government employees can increase and can be responsible for carrying out their duties as a civil servant